“Efecto de fungicidas de protección y sistémicos en el control de hongo alternaria sp. En cebolla china (allium fistulosum) en Lamas” - Granda Jiménez, Anival (2001)
The purple stain of the Chinese onion (Allium fistolosum) caused by the mushroom it would A/ternaria sp., it is one of the illnesses of importance for the cultivation in San Martín Departmet)t. lt is controlled through applications to the area to foliate in several growth stages. In order to evaluate the effects of the applications of contact fungicides (Triflumizole, Fentinacetato, Tolyfluanid) and systemic (Cimoxanil + Mancozeb, Citrex) in the control of the pathogen, a rehearsal settled down in the "El Retorno" farm in the Lamas county, on a design Block complete randomizado with four repetitions. The evaluations to determine the effect of the fungicides were carried out evaluating the level of incidence in plants and leaves, the number of stains for leaf, severity of the illness, toxicity and cultivation yield in fresh. The results pointed out that the fentinacetato to the dose of 1 g /1 presented 33,60 % to 45,56 % of incidence in plant, 13,35 to 22,20 % of incidence in leaves, 1,00 to 1,66 stains for leaf, 9,67 to 11,39 %, without toxicity to the cultivation, 14 937,50 Kg /ha and relationship cost benefit of 50, 82% gave the best control continuad in arder of importance Cimoxanil +Mancozeb 3,0 g /1, Citrex 2 mi /1, Triflumizole, 1 g /1 and fentinacetato 0,5 g /l.